Debunking the ‘Nerd’ Myth: Doing Action Research with First-year Engineering Students in the Academic Writing Class - Lievens, Jeroen (Journal of Academic Writing, 2012)
First-year engineering students are disinclined to view writing skills, and communication skills at large, as a core element of the engineering curriculum. Instead of arguing away this student skepticism, we aimed to harness it by way of an action research project in the writing class: students were challenged to find out for themselves whether, and if so, which communication skills are important for professional engineers and to write out their recommendations for the curriculum in a brief research paper. The teaching staff supported the research project by providing an online questionnaire, which 443 engineers filled out on the students’ invitation, and by offering support sessions on academic writing, research and ict skills. What the students learned from the questionnaire, was that the respondents spend very a significant amount of their working time communicating, while many of them struggle with several aspects of both written and oral communication. Abandoning their initial beliefs, the students recommended in their papers that communication skills take a central place in the engineering curriculum. The action research approach, in other words, helped students develop not only their academic writing skills, but also their attitudes towards communication courses and more generally, their understanding of 21st century engineering.